The impact of internal control on performance of small and medium-sized enterprises in an emerging economy / Nguyen To Tam and Le Anh Tuan - To Tam, Nguyen; Tuan, Le Anh (Universiti Teknologi MARA, 2021)
This research studied the impact of internal control on financial performance of small and medium-sized enterprises (SMEs) in an emerging economy. The studying framework was derived from the Agency Theory to examine the relationship between internal control and organizational performance in SMEs. The paper used a survey and non-probability sampling and applied regression analysis to assess this effect on SMEs in Hanoi, Vietnam. Internal control consisted of five elements (including control environment, risk assessment, control activities, information and communication systems, and monitoring activities) by COSO. SME’s performance was measured by ROA primarily. This research analyzed data using SPSS and Smart PLS software’s. Using a sample of 94 respondents, the results show that the control environment which is a dimension of internal control has a positive influence on the performance of SMEs in this case. Other dimensions of internal control that are control activities, information and communication system, risk assessment, and monitoring activities showed insignificant impacts on performance of SMEs but the results still give some meaningful insights for SMEs in Vietnam. The results of this paper provide practical insights on the role of internal control for researchers and business managers.